Implementasi Quick Response Code Indonesian Standard (QRIS) Untuk Pelaku Usaha Di Pasar Tradisional : Studi Kasus Pada Pasar Tradisional Di Kota Kupang - Jeanet Putri Shintya Nubatonis; Fransina W. Ballo; Novi Theresia Kiak (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
In the development of financial technology, many payment system innovations have emerged, one of which is the Indonesian Standard Quick Response Code (QRIS). This research aims to determine the implementation of QRIS for business actors in the Kupang City Traditional Market. This research uses a qualitative approach, with data collection methods conducting interviews, observation, documentation. The results of this research show that the Quick Response Code Indonesian Standard (QRIS) is an electronic payment tool to make it easier for people to carry out transactions. Through QRIS, people can feel the ease of making transactions anytime and anywhere, even outside bank operational hours. However, in its implementation there are several obstacles, namely a weak internet connection so that the transaction process carried out by traders is hampered, the cellphones owned by traders are not yet sophisticated so they cannot make transactions, lack of knowledge and a 0.3% deduction from the transaction value.